Evaluation of Sample Preparation Methods from Rice Seeds and Seedlings Suitable for Two-Dimensional Gel Electrophoresis - Wongpia,A. (Humana Press, 2015)
© 2014, Springer Science+Business Media New York. In a proteomic study, sample preparation is very important because it affects the quality of protein profiles on two-dimensional gel electrophoresis (2-DE). This study investigated the suitability of four protein extraction methods—direct lysis buffer extraction, trichloroacetic acid (TCA)/acetone precipitation, phenol extraction, and polyethylene glycol (PEG) fractionation—from rice seeds and seedlings (Oryza sativa L. ssp. indica cv. Khao Dawk Mali 105). The effectiveness of these methods was evaluated by the protein quantity and the 2-DE profiling quality. This included the number of protein spots, the consistency and uniqueness of protein spots, and their distribution in different ranges of pI and molecular weight (Mr). For protein quantity, the phenol and direct lysis extraction methods gave the highest protein yield in rice seeds and rice seedlings, respectively. However, in terms of the quality of 2-DE profiles, samples prepared by the TCA/acetone and phenol methods exhibited higher protein resolution and more spots than the protein profile derived from direct lysis extract. In addition, TCA/acetone method had the efficiency for high Mr protein detection. PEG fractionation provided the best 2-DE pattern in terms of resolution, number of spots, minimal streaking, and reproducibility. Moreover, PEG fractionation was better for determining low Mr basic proteins.